Upaya Peningkatan Minat Baca Murid SD 112318 Sipare-pare Tengah - Indah Wulan Sari Batubara; Elda Anzely Hasibuan; Mispa Herlina Wati Sipahutar; Intan Sari Tanjung; Abdi Syahputra; Arif Munandar; Nurul Hayati Panjaitan; Nefi Damayanti (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Efforts to increase children's interest in reading are a shared responsibility, between librarians, teachers, parents, and the community are directly responsible for developing interest in reading. To develop interest in reading, children need to be given stimuli that encourage interest in reading students themselves. Efforts to encourage students to read as many books as possible are not effective. Forcing children to buy books is also unethical. One of the activities carried out to develop and increase interest in reading for each student is the provision of subsidized textbooks. This book is a reference for students and teachers in schools where textbooks and the learning process always try to complement the reading. Books that stimulate children's interest in reading. Increasing interest and interest in reading, especially among students, requires effective library management. The purpose of this research is to increase students' reading interest which is still very low. The location of this survey is SD Negeri 112318, Merbau Regency, Sipare-Pare Tengah. and has a learning theme for grades 3 and 5. Keywords: Reading Interest, Librarian, Library